CASTE VARIATION OF SOME PLACENTAL ISOZYMES - KUMARI, S. ANITHA; KUMAR, N. SREE RAM; CHITRA, K. Y. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
A total of 526 Human placentae from individuals belonging to three different caste groups living in Andhra Pradesh, South India were studied with respect to six different isozyme markers Superoxide dismutase (SOD), Malate dehyrogenase (MDH), Glutamic oxaloacetic transaminase (GOT), Lactate dehydrogenase (LDH), Inorganic pyrophosphatase (IP) and Glutamate dehydrogenase (GDH). Rare variants were found in case of SOD, MDH and GOT while no electrophoretic variant was found in case of LDH, IP and Glutamate dehydrogenase isozyme systems.